(untitled) (Psychology Travelogs, 2021)
The article analyzes some features of the development and communication of children with autism spectrum disorders. It is emphasized that children with autism have impaired social interaction, which can be hidden at an early age in the form of hidden deficiencies in the common sense and relational response, which makes them more isolated. It is stated that children with autism are characterized by such traits as passivity, lack of interest in others. Modern domestic and foreign researchers note that one of the main shortcomings that prevent the successful adaptation of children with ASD is a violation of communication skills. Therefore, this violation manifests itself in the form of lag or lack of spoken language, inability to initiate or maintain dialogue, as well as in the form of stereotypical statements and a number of other specific features. It is also emphasized that based on the understanding that communication skills in children with ASD do not develop independently, it is necessary to use special correction techniques for their formation. Despite the significant amount of research on the development of communication skills in children with ASD, it should be noted that while there is no universal system for developing these skills in children with ASD, so need the attention of scientists and practitioners, research aims to create and test special correction techniques communication skills in children with ASD. As a result of the analysis of the peculiarities of development and communication of children with autism, it can be noted that the process of formation of communication skills in children with ASD depends on the individual personality of the child, the age of the process of communication skills with children. Also, it should be emphasized that the use of alternative communication methods to organize interaction with children with ASD, contribute to the establishment of contact between children and adults. With the help of additional communication, children can express their own needs, which greatly facilitates the understanding and interaction of the child and the adults around him. As the process of inclusive education in Ukraine is gaining momentum, a deeper study of the peculiarities of development and communication of children with ASD, requires detailed research and improvement of methods and techniques of their development.